ANALISIS STUDI LITERATUR: STRATEGI OPTIMALISASI BANTUAN OPERASIONAL SEKOLAH (BOS) UNTUK PENDIDIKAN DASAR BERKUALITAS - Julia, Alfiani Nur; Ahmad, Masduki (Jurnal Manajemen Pendidikan, 2025)
The School Operational Assistance (BOS) program is a strategic policy of the Indonesian government aimed at supporting the operational financing of basic education and ensuring equitable and inclusive access to quality education. However, the utilization of BOS funds at the school level has often not been fully effective in enhancing the quality of learning. This study aims to analyze strategies for optimizing the use of BOS funds through a literature review of 30 national and international academic journals published between 2021 and 2025. The method employed is a systematic literature review, focusing on scholarly documents that meet inclusion criteria based on topic relevance, publication year, and academic credibility. The findings indicate that while BOS has significantly contributed to the sustainability of basic education services, its use remains largely administrative and insufficiently focused on quality improvement efforts such as teacher development, literacy and numeracy programs, and inclusive education initiatives. Challenges in BOS implementation include limited managerial capacity at schools, delays in disbursement, low community involvement, and inflexible policy guidelines. Therefore, reforms are needed in planning, supervision, and technical guidance to make BOS more adaptive to local needs and quality-oriented.